A Conceptual Paper on the Relationship between Transformational Leadership and Employee Engagement - Wen, Ivan Vun Kai; Choi, Sang Long (Business Management and Strategy, 2023)
The importance of a transformational leader’s capabilities is beyond direct guidance, rather it extends towards securing lasting outcomes and sustained performance. Considering multiple facets of enhancement are inevitable, the various dimensions of transformational leadership enable scholars and industrial practitioners to pinpoint the pivotal aspects of transformational leadership responsible for employee engagement. Expanding on existing theories, it becomes vital to establish the traits of transformational leadership that significantly influence an employee engagement. Thus, this conceptual paper shall fortify the theoretical structure by investigating the relationship of transformational leadership (idealized influence, individualized consideration, inspirational motivation, intellectual stimulation, employee appreciation, performance expectation) and the correlations towards employee engagement, through comprehensive literature reviews, validating the significance of the relationship. From the findings of this study, the relationship between transformational leadership and employee engagement was justified to be significant. Future studies may leverage the expanded framework proposed in this conceptual paper to conduct quantitative studies in specific geographic areas or industries, further validating the effectiveness of these variables.